1988
DOI: 10.1177/074355488833010
|View full text |Cite
|
Sign up to set email alerts
|

Explanations of Sexual Assault among Violent Delinquents

Abstract: Despite recent attention both to sex offenders and violent delinquents, there is little empirical knowledge on the causes and correlates of juve nile sex offenses. Juvenile sex offenders (N = 34) were identified among a sample of chronic violent offenders (N = 242) from official records and face-to-face interviews. Juvenile sex offenders were 14. 1 percent of the sample. Sex offenders more often lived with their birth parents while violent offenders often lived in single parent families. Sex offenders had fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 18 publications
3
53
1
3
Order By: Relevance
“…Although much of this work has focused on adult perpetrators of child sexual abuse, some studies have found a relationship between child maltreatment experiences and adult rape convictions (Dhawan & Marshall, 1996), aggression towards women (Fagan & Wexler, 1988), and generalized aggression as adults (Widom, 1989(Widom, , 2000, each suggesting that childhood maltreatment may increase an individual's risk for future sexual misconduct. Furthermore, a large-scale study by Malamuth and colleagues (1991) identifi ed childhood maltreatment as a critical distal factor in the development of sexually violent behavior towards women.…”
Section: Childhood Abuse Experiencesmentioning
confidence: 99%
“…Although much of this work has focused on adult perpetrators of child sexual abuse, some studies have found a relationship between child maltreatment experiences and adult rape convictions (Dhawan & Marshall, 1996), aggression towards women (Fagan & Wexler, 1988), and generalized aggression as adults (Widom, 1989(Widom, , 2000, each suggesting that childhood maltreatment may increase an individual's risk for future sexual misconduct. Furthermore, a large-scale study by Malamuth and colleagues (1991) identifi ed childhood maltreatment as a critical distal factor in the development of sexually violent behavior towards women.…”
Section: Childhood Abuse Experiencesmentioning
confidence: 99%
“…On a découvert que les agresseurs sexuels adolescents provenaient généralement de milieux familiaux socialement isolés (Fagan et Wexler, 1988;Fehrenback, Smith, Monastersky et Deisher, 1986), et cette aliénation chez les enfants et les adolescents est le résultat de liens d'attachement pauvres entre parent et enfant (Le Frenière et Sroufe, 1984;Sroufe, 1983). De plus, les agresseurs sexuels adolescents proviennent de familles perturbées où ils ont subi des abus ou été négligés (Awad, Saunders, et Levene, 1984).…”
Section: Les Problèmes D'attachementunclassified
“…Quelques comptes rendus de recherches étayent l'idée selon laquelle la solitude est commune aux agresseurs sexuels (Awad et al, 1984;Fagan et Wexler, 1988 ;Saunders, Awad et White, 1986;Tingle et al, 1986), mais jusqu'à très récemment, il n'existait pas d'étude systématique des déficiences dans les liens d'intimité chez les agresseurs sexuels. Il existe toutefois maintenant deux rapports récents portant à la fois sur la solitude et sur la défi-cience d'intimité chez ces hommes.…”
Section: Intimité Et Solitudeunclassified
“…A recurring finding is the presence of a history of sexual and/or physical abuse, which has been demonstrated more frequently in sex offenders than in nonsex offenders (Fagan & Wexler, 1988;Hastings, Anderson, & Hemphill, 1997;Jonson-Reid & Way, 2001;Milloy, 1994). Mixed results have been demonstrated with respect to other characteristics (e.g.…”
mentioning
confidence: 99%